Kinetic studies on cooking of pineapple bakery jam - Pua, Ming Yee; Shamsudin, Rosnah; Hamzah, Azman; Endan, Johari (Academic Journals, 2011)
Cooking rate of pineapple bakery jam was investigated and the effect of cooking temperature, stirring speed and batch volume on rate constant was examined. The linear relationship between the logarithmic total soluble solids gain ratios of cooked jam and the cooking time showed that the cooking rate followed the equation of first-order chemical reaction. In this present study, the cooking rates were increased with cooking temperature and stirring speed, but it decreased with increasing batch volume. The activation energy of cooking process was 42.49 kJ mol-1. The recommended cooking temperature for cooking of pineapple bakery jam was 90°C as the jam was burnt on the surface of the cooker and undesirable caramel flavour was resulted at cooking temperature of 100°C. Present investigation of cooking rate constant will be useful in designing more efficient jam cookers with higher ratio of effective heating surface to batch volume of fruit pulp.